AY LYRAE SUPERHUMPS PHOTOMETRY - Smykov, V. P. (Одеські астрономічні публікації, 2017)
During the superoutburst the superhumps with an amplitude of 0.2 mag in BV were observed. The superhumps period changed from 90 min at the maximum of the outbursts (12.8 V) up to 108 min at V = 13.2. These values are less than that obtained by previous authors.